Obstetrical Variables Leading to Successful Vaginal Birth After a Cesarean Section in a Tertiary Care Hospital of Pakistan - Shehzadi, Huma; Choudry, Abeera; Mehmood, Fatima; Riaz, Tahira; Shafique, Sadaf; Zahra (Pakistan Armed Forces Medical Journal, 2025)
Objectives: To determine the frequency of vaginal birth and association of it with obstetrical factors that led to successful vaginal delivery after a previous one cesarean section in a tertiary care hospital.Study Design: Cross-sectional study.Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Apr to Sep 2022.Methodology: A total of 340 pregnant females who fulfilled the selection criteria were enrolled after written informed consent. All patients underwent a trial of labor and were followed till the delivery of the baby. Obstetrical factors were noted down. Successful vaginal birth after trial of labor was noted down and findings were subjected to statistical analysis. Results:  The mean age (in years) of the females was 27.713.05. Vaginal Birth After a Cesarean occurred successfully in 70.6% females. The obstetrical factors that were significantly associated with successful Vaginal Birth After a Cesarean were inter-pregnancy interval (p=0.01), cervical dilatation (p=0.013), cervical effacement (0.019) and duration of active phase of labor (p=0.043).Conclusion:  Successful vaginal delivery was frequently seen in females who had previous one cesarean section i.e. in 70.6% females and had significant association with inter-pregnancy interval, cervical dilatation, cervical effacement and duration of active phase of labor.